Updating midlife : psychoanalytic perspectives - Montero, Guillermo Julio, ....-; Ciancio de Montero, Alicia Mirta, ....- (London : Karnac, 2013)
"Midlife" is a concept used everywhere and from many different vertexes, though mostly imprecisely, even within the psychoanalytic paradigm. This book tries to settle its proper meaning through the challenge of laying the foundations for the development of a true psychoanalytic metapsychology for "midlife", something that the editors believe in psychoanalysis was lacking. From this viewpoint, they invited fourteen renowned psychoanalysts to share their ideas about the issue. The outcome of that work is Updating Midlife: Psychoanalytic Perspectives, which, in addition to the various contributions, includes an introductory paper by the editors. This book is a true step forward in the development of a specific metapsychology for "midlife".
Keywords: Middelbare leeftijd; Psychoanalyse